Peran Kompetensi Serta Efikasi Diri Pada Prestasi Kerja Pegawai Tetap Teller Bank di Palembang - Sulistyawati, Maria Fransiska Sri; Septianna Sri Ratnasari, Agatha (Catholic University Musi Charitas, 2022)
The purpose of this study was to determine and examine the effect of the competence variable (X1) and self-efficacy variable (X2) on the performance variable (Y) of bank teller employees in Palembang. The sample of this research respondent is specifically for permanent employees of bank tellers who work in Palembang. The data used are primary data and secondary data. The sampling technique used in this research is the convenience method. The convenience method is that every permanent employee of a bank teller in Palembang has the same opportunity and is willing to fill out or choose an answer from the statement submitted in the questionnaire. Data analysis techniques used include: validity test, reliability test, and classical assumption test. Hypothesis testing using multiple linear regression analysis using SPSS 26 for windows program. The results of the study stated that the competence variable (X1) and self-efficacy variable (X2) had a positive and significant effect on the performance of bank teller employees in Palembang.